Safeguarding Consumers: The Role of Industry and Trade Office in Countering Monopolistic Practices and Ensuring Business Protection - Diab, Ashadi L.; Iswandi, Iswandi; Yaqub, Andi; Muthalib, Lian M.; Baharuddin, A. Zamakhsyari (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
This research investigates (1) the significance and function of the consumer protection and anti-monopoly division within the Industry and Trade Office in supporting business entities, and (2) the measures that the Industry and Trade Office should adopt moving forward to address regulatory needs, particularly concerning anti-monopoly and business competition, in Kendari. This study employs Conflict Theory and Symbolic Interaction Theory as its theoretical framework. The findings reveal that (1) the relevant division plays a crucial role in conducting Consumer Protection Socialization as a program managed by the Industry and Trade Office of Southeast Sulawesi Province, involving business entities, consumers, community members, and university students; (2) activities centered around consumer protection and anti-monopoly implemented by the relevant division are as described by the Head of the Consumer Protection and Trade Order Division: The Consumer Protection Monitoring System serves as a medium for consumer complaints and information related to consumer protection to be integrated into the system at the Provincial Office responsible for trade, aiming to enhance service to consumers in lodging complaints from those who feel wronged.